Impact of surface wettability on S-layer recrystallization: a real-time characterization by QCM-D - Iturri, Jagoba; Vianna, Ana C.; Moreno-Cencerrado, Alberto; Pum, Dietmar; Sleytr, Uwe B.; Toca-Herrera, José Luis (Beilstein Journal of Nanotechnology, 2017)
Quartz crystal microbalance with dissipation monitoring (QCM-D) has been employed to study the assembly and recrystallization kinetics of isolated SbpA bacterial surface proteins onto silicon dioxide substrates of different surface wettability. Surface modification by UV/ozone oxidation or by vapor deposition of 1H,1H,2H,2H-perfluorododecyltrichlorosilane yielded hydrophilic or hydrophobic samples, respectively. Time evolution of frequency and dissipation factors, either individually or combined as the so-called Df plots, showed a much faster formation of crystalline coatings for hydrophobic samples, characterized by a phase-transition peak at around the 70% of the total mass adsorbed. This behavior has been proven to mimic, both in terms of kinetics and film assembly steps, the recrystallization taking place on an underlying secondary cell-wall polymer (SCWP) as found in bacteria. Complementary atomic force microscopy (AFM) experiments corroborate these findings and reveal the impact on the final structure achieved.
Keywords: bacterial S-layers; Quartz crystal microbalance with dissipation monitoring (QCM-D); recrystallization kinetics; surface wettability